Peningkatan Proses Dan Hasil Belajar IPAS Menggunakan Model Make A Match Berbantuan Media Wordwall - Rika Arini; Sundahry; Puput Wahyu Hidayat (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
Abstract This research is motivated by the low learning outcomes of IPAS, which is 45.8% of students in grade V of SD Negeri 187/II Kuning Gading. This research aims to improve the learning process and outcomes of IPAS through the application of the Make A Match model with the help of Wordwall media. The method of this research is a two-cycle Classroom Action Research (PTK). The research sample was 24 students. Data is collected through observation, testing, and documentation. The results showed an increase in teacher performance from cycle I 82.3%, cycle II increased by 94.1% and learning completeness from cycle I 70.8% cycle II increased by 91.6%. Student activities are consistent in the good to very good categories. The Make A Match model is a partner-based learning model that has been proven to be able to improve the learning outcomes of IPAS students in grade V of SDN 187/II Kuning Gading. This research contributes to innovative learning through the use of technology as an interactive media that is able to encourage student enthusiasm and create an active, fun, and meaningful learning atmosphere. The novelty of this research lies in the application of the Make A Match model assisted by Wordwall which is focused on improving the understanding of more complex natural concepts of rich Indonesian material in IPAS learning in grade V of elementary school. It can be concluded that the use of technology in learning is not only effective in improving learning outcomes, but also training students' readiness to face technological developments in the digital era. Keywords: Learning processes and outcomes; Cognitive IPAS; Make A Match, Wordwall.